Influence of Testing Position on the Reliability of Hip Extensor Strength Measured by a Handheld Dynamometer - Lue, Yi-Jing; Hsieh, Ching-Lin; Liu, Mei-Fang; Hsiao, Shih-Fen; Chen, Shu-Mei; Lin, Jau-Hong; Lu, Yen-Mou (The Kaohsiung journal of medical sciences, 2009)
Hip extensors belong to an important muscle group that controls standing, walking and other functional activities. The prone position (PP) is commonly used to measure the strength of the hip extensors; however, the reliability of such measurements is poor. The aim of this study was to determine the effect of different testing positions, that is, the PP and the prone standing position (PSP), on the reliability of measurements of hip extensor strength. Intrasession reliability and interrater reliability studies were performed on 47 and 16 normal subjects, respectively. The muscle strength of the hip extensors was tested in both the PP and PSP. A handheld dynamometer and break test were used to measure the strength. Relative reliability and absolute reliability were assessed in both PP and PSP. For relative reliability, the intraclass correlation coefficient (ICC) was used to examine the level of reproducibility among measurements. Absolute reliability, the smallest real difference (SRD), was used to provide information on measurement error. The results showed that the reliability was better in PSP than in PP. For relative reliability, the values of ICCs were excellent in the intrasession reliability study, in both PP (ICC 1,3 = 0.92) and PSP (ICC 1,3 = 0.94). However, the interrater reliability was only excellent in PSP; the ICC 2,3 were 0.92 in PSP and 0.65 in PP. For absolute reliability, the values of the SRD were much lower in PSP (29.8) than in PP (71.8), indicating that the measurement of muscle strength in PSP was more stable and had smaller measurement error than in PP. Changing the testing position from the traditional “prone” to “prone-standing” effectively improved both the relative reliability and the absolute reliability.